Stomatal development and gene expression in rice florets - Bertolino, Lígia T.; Caine, Robert S.; Zoulias, Nicholas; Yin, Xiaojia; Chater, Caspar C.C.; Biswal, Akshaya; Quick, William P.; Gray, Julie E. (Oxford University Press, 2022)
Stomata play a fundamental role in modulating the exchange of gases between plants and the atmosphere. These microscopic structures form in high numbers on the leaf epidermis and are also present on flowers. Although leaf stomata are well studied, little attention has been paid to the development or function of floral stomata. Here, we characterize in detail the spatial distribution and development of the floral stomata of the indica rice variety IR64. We show that stomatal complexes are present at low density on specific areas of the lemma, palea and anthers and are morphologically different compared to stomata found on leaves. We reveal that in the bract-like organs, stomatal development follows the same cell lineage transitions as in rice leaves and demonstrate that the overexpression of the stomatal development regulators OsEPFL9-1 and OsEPF1 leads to dramatic changes in stomatal density in rice floral organs, producing lemma with approximately twice as many stomata (OsEPFL9-1_oe) or lemma where stomata are practically absent (OsEPF1_oe). Transcriptomic analysis of developing florets also indicates that the cellular transitions during the development of floral stomata are regulated by the same genetic network used in rice leaves. Finally, although we were unable to detect an impact on plant reproduction linked to changes in the density of floral stomata, we report alterations in global gene expression in lines overexpressing OsEPF1 and discuss how our results reflect on the possible role(s) of floral stomata.